Conceptualizing grade inflation. (October 2020) - Tyner, Adam; Gershenson, Seth
Abstract: Evidence of grade inflation in U.S. high schools is often misinterpreted due to confusion about how grade inflation is, or should be, defined. This note reduces the confusion by introducing a typology of grade inflation and discussing the implications of each type. We then provide empirical examples of each type of grade inflation using transcript and test-score data from Algebra I classes in North Carolina over a recent ten-year period. Year-specific (static) grade inflation has been, and remains, higher in schools serving relatively disadvantaged student populations; however, differential changes over the past ten years (what we term dynamic grade inflation) have significantly narrowed the socioeconomic gap in static grade inflation.